2008
DOI: 10.3174/ajnr.a1092
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Body Tumors: Objective Criteria to Predict the Shamblin Group on MR Imaging

Abstract: BACKGROUND AND PURPOSE:MR imaging is an established method for diagnosis and surgical planning of carotid body tumors (CBTs). However no studies have elaborated preoperative objective criteria to predict the Shamblin (surgical) classification of CBTs, an important predictor of vascular morbidity. The purpose of this study was to establish criteria to accurately predict the Shamblin group on preoperative MR imaging for a uniform reporting system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 18 publications
2
103
0
6
Order By: Relevance
“…3,4 .In our series, cranial nerve deficits occurred in three patients, involving the VII, X and XII pairs which is concordant with other series. Power et al demonstrated that preoperative embolization may have some benefits for the surgical approach, especially relating to surgical bleeding, but the patients that they followed up did not present any differences in definitive neurological sequelae.…”
Section: Discussion:-supporting
confidence: 78%
See 3 more Smart Citations
“…3,4 .In our series, cranial nerve deficits occurred in three patients, involving the VII, X and XII pairs which is concordant with other series. Power et al demonstrated that preoperative embolization may have some benefits for the surgical approach, especially relating to surgical bleeding, but the patients that they followed up did not present any differences in definitive neurological sequelae.…”
Section: Discussion:-supporting
confidence: 78%
“…Power et al demonstrated that preoperative embolization may have some benefits for the surgical approach, especially relating to surgical bleeding, but the patients that they followed up did not present any differences in definitive neurological sequelae. 3,12 Although our series did not have any cases of malignant chemodectoma, it is important to mention that the malignant potential has been reported to be around 2-6 % in the literature, most frequently with metastasis to regional lymph nodes. 15 .…”
Section: Discussion:-mentioning
confidence: 99%
See 2 more Smart Citations
“…18 As the carotid body tumor arises from the wall of the common carotid artery, it tends to completely fill the crotch of the bifurcation 2 and encase the ICA and ECA. 19 In our experience, schwannomas do not fill the crotch of the carotid bifurcation because we could identify the angle of the bifurcation in all 4 patients with SCSC splaying the carotid arteries. We found the SCSC merely separating the ICA and ECA as well as the arteries stretched about the tumor; yet the contact between them did not exceed 180°of the vessel circumference.…”
Section: 11mentioning
confidence: 99%